Exploring the Common Ground: A Comparative Analysis of Zoroastrianism and Islam: A Comparative Analysis of Zoroastrianism and Islam - Mostofa, Shafi Md (Journal of the Asiatic Society of Bangladesh, Humanities, 2024)
Islam and Zoroastrianism share remarkable similarities in their theological and eschatological beliefs. They both believe in the oneness of God, with different names (Ahura Mazda for Zoroastrians and Allah for Muslims) but similar attributes of omnipotence, omniscience, and omnipresence. Both religions acknowledge archangels, with Zoroastrianism recognizing six and Islam recognizing four, along with other minor angels. Both religions consider humans as the pinnacle of creation and emphasize the establishment of justice and truth on earth. They share beliefs about the nature of the universe as a creation of God, and the role of prophets as messengers of God. Prayer is considered important in both religions, with similar practices of five daily prayers (Salat in Islam, Gah Worship in Zoroastrianism) and similar beliefs about the afterlife, including the immortality of the soul, resurrection of the dead, balance of judgment, heaven and hell, and the existence of a bridge to be crossed after death (Chinvat Bridge in Zoroastrianism, Al-Siraat in Islam). Ethical codes emphasizing purity of mind and body are also similar in both religions. Thus, this article argues, using intertextuality theory, that Islam is not a new beginning but rather a continuation of earlier revelations, such as Zoroastrianism. This perspective further suggests that Zoroastrianism can be categorized within the Abrahamic traditions. JASBH, Vol. 69(2), 2024, pp. 223-237